2014
DOI: 10.1080/15427609.2014.906739
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Interplay of Processes Across Multiple Time-Scales: Illustration With the Intraindividual Study of Affect, Health, and Interpersonal Behavior (iSAHIB)

Abstract: Human development is characterized by the complex interplay of processes that manifest at multiple levels of analysis and time-scales. We introduce the Intraindividual Study of Affect, Health and Interpersonal Behavior (iSAHIB) as a model for how multiple time-scale study designs facilitate more precise articulation of developmental theory. Combining age heterogeneity, longitudinal panel, daily diary, and experience sampling protocols, the study made use of smartphone and web-based technologies to obtain inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 30 publications
2
106
0
Order By: Relevance
“…Interested readers are encouraged to consult [75] for further detail regarding this survey. These sets of questionnaires can be categorized by their frequencies of response, namely once (background information), burst (pre/post burst visits), daily (daily information), and event-contingent (interaction/conversation information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interested readers are encouraged to consult [75] for further detail regarding this survey. These sets of questionnaires can be categorized by their frequencies of response, namely once (background information), burst (pre/post burst visits), daily (daily information), and event-contingent (interaction/conversation information).…”
Section: Methodsmentioning
confidence: 99%
“…The ground-truth validation data was drawn from the Intra-individual Study of Affect, Health, and Interpersonal Behavior [75]. The data collection campaign was conducted with 150 participants from the Pennsylvania State University community, ages range from 18 – 90 years (mean = 47.10, standard deviation = 18.76).…”
Section: Case Studymentioning
confidence: 99%
“…Comprehensive descriptions of the National Survey of Daily Experiences (NSDE; Almeida, McGonagle, & King, 2009), and the Intraindividual Study of Affect, Health, and Interpersonal Behavior (iSAHIB; Ram et al, 2014) can be found in the noted references, while specific details relevant to the present study are given below.…”
Section: Methodsmentioning
confidence: 99%
“…The Intraindividual Study of Affect, Health, and Interpersonal Behavior (iSAHIB; Ram et al, 2014) worked with 150 adults (51% women) recruited from the Pennsylvania State University and surrounding community, and purposively stratified by gender and across the adult life span in 18–24 ( n =22), 25–34 ( n =27), 35–49 ( n =30), 50–64 ( n =41), 65+ ( n =30) year age-bins. Participants were between 19 and 89 years of age ( M = 47.10, SD = 18.76), had obtained between 2 and 24 years of formal education ( M = 16.36, SD = 3.90), and had between 0 and 6 children ( M = 1.5, SD = 1.41).…”
Section: Methodsmentioning
confidence: 99%